2010
DOI: 10.1016/j.joca.2010.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Association study between polymorphisms in selenoprotein genes and susceptibility to Kashin-Beck disease

Abstract: GPX1 Pro198Leu is a potential genetic risk factor in the development of KBD and the GPX1 Leu allele is significantly associated with higher KBD risk among the Chinese Han population and with lower GPX enzyme activity. The expression of apoptosis related molecules in KBD patients significantly differs from controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
2
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(72 citation statements)
references
References 29 publications
1
66
2
3
Order By: Relevance
“…All the evidences revealed that genes might play a key role in the pathogenesis of KBD besides environmental factors. Recently, some susceptibility genes SNPs such as GPX1 [33], IL-1β [34], etc. have also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…All the evidences revealed that genes might play a key role in the pathogenesis of KBD besides environmental factors. Recently, some susceptibility genes SNPs such as GPX1 [33], IL-1β [34], etc. have also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Albeit, after multiple testing, no significant associations remained. Xiong et al (82) evaluated whether the D2-Thr92Ala variant could influence the risk of Kashin-Beck disease, a chronic endemic osteochondropathy found in selenium-deficient areas of China, south-east Siberia, and North-Korea, and found no significant association of this genetic variant with the disease. The interaction between selenium or iodine deficiency, genetic variation in deiodinases and health effects is a scarcely investigated domain and may be a worthwhile field of future research.…”
Section: Iodine and Selenium Deficiency And Effect Of Polymorphisms Omentioning
confidence: 99%
“…IDH2 plays a role in the metabolism of glutathione, which composes the important glutathione/glutathione disulfide anti-oxidant protecting system of the human body [18]. As a major component of the glutathione/glutathione disulfide anti-oxidant protection system, glutathione peroxidase1 (GSH-Px1) is known to be associated with the risk of KBD [19]. The protective effect of GSH-Px1 largely depends on the presence of selenium, while low selenium is an important environmental risk factor for KBD.…”
Section: Discussionmentioning
confidence: 99%